Discrimination based on Religion or Belief in the Field of Work - Turčinović, Filip; Bakić, Vera; Stojković Zlatanović, Sanja (Sociološki pregled, 2021)
The paper aims to research the necessity of the policy and legal protection of freedom of religion at the workplace, as well as to support the prevention of discrimination of the employees on grounds of religion. The sociological and legal normative method regarding the implementation of the international principle of Dignity at Work, accompanied by the integrated and holistic approach in the research, has been applied. The basic research questions are defined as follows – whether the majority, declarative guarantee of freedom of religion by the provisions of the Constitution, as well as by positive legal documents, is sufficient for the protection against religious discrimination in the domain of labour, and how to increase the scope and level of individual protection of freedom of religious expression, in a way not jeopardizing the interests of the employer in the conditions of domination of economic principles in business, as well as in the labour market, in addition establishing a balance with social goals in terms of achieving goals of the sustainable development agenda.